APPLICATION OF FISH EATING GYMNASTICS (GEMARI) TO IMPROVE GROSS MOTOR SKILLS OF CHILDREN AGED 5-6 YEARS IN SRITANJUNG KINDERGARTEN BANGUNSARI SONGGON BANYUWANGI - Novitasari; Riris Wahyuningsih; Fitriatul Masruroh (International Conference on Humanity Education and Society (ICHES), 2023)
As the earliest educational institution for children, Early Childhood Islamic Education (PIAUD) has a role in developing one aspect: gross motor development for early childhood. Gross motoric development can be realized if learning can be carried out in a pleasant, comfortable, and conducive manner. One of the stimuli by exemplifying some fun movements is fond of eating fish gymnastics in early childhood. In fact, in society, there are many children whose gross motor skills are not stimulated. They prefer to play with gadgets for too long, which cause their gross motor skills to develop less because they tend to be silent. For this reason, an appropriate stimulus is needed to make it easier for children to explore their gross motor development. Fish-eating gymnastics is a suitable method for improving gross motor development skills in early childhood. Sritanjung Kindergarten Bangunsari Songgon Banyuwangi is a kindergarten institution that implements fish-eating gymnastics. This study aimed to determine the application of fish-eating gymnastics and the supporting and inhibiting factors of fish-eating gymnastics implementation. This study used a qualitative approach, with basic research. Data analysis techniques were carried out interactively through four stages data collection, data reduction, presentation, and conclusion. This research was conducted at Sritanjung Kindergarten Bangunsari Songgon Banyuwangi. The research subjects were group B teachers, principals and 11 group B students of Sritanjung Kindergarten. The final accumulation results showed the gross motor development achievements of Sritanjung Kindergarten students in the 2022-2023 academic year in group B, totaling 11 children with an assessment using 3 indicators, resulting in 8 children developing very well and 3 children developing as expected. This method was supported by the existence of 2 factors, namely supporting factors and inhibiting factors.